Aplikasi Diagnosa Epliepsi dengan Metode Certainty Factor pada Rumah Sakit Umum Daerah Kota Pinang - Febrianti Mandasari; Antoni; Tasliyah Haramaini (Bulletin of Computer Science Research, 2022)
In the development of computer technology, computer technology has become an inherent part of human life when it comes to solving a more complex problem in various areas, including education, health, etc. One of the applications of information technology in the health field is an expert system for the identification of epilepsy. An expert system is a computer system that wants to replicate the decision making ability of an expert in all aspects. Epilepsy is the second most common neurological disorder in humans following stroke. The shortage of epilepsy specialists and the lack of tools to deal with epilepsy requires a system that can help the problem in the form of an expert system using certainty factor method to ensure that there are no misdiagnosis and to assist doctors in diagnosing epilepsy in patients quickly. As a research type, explanatory research is used using primary and secondary data types, the data collection method used is the method of interviewing and literature studies and the method of certainty factor with front chain reasoning techniques. This application requires data on disease symptoms, certainty factors of expert value and certainty factors of patients to get a confidence level for epilepsy diagnosis. Based on the results of the study, it can be concluded that the system is capable of providing confidence values, can diagnose epilepsy based on the symptoms entered by the user, and can provide a solution for epilepsy.